Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1074/jbc.m708597200
|View full text |Cite
|
Sign up to set email alerts
|

Complex I Is the Major Site of Mitochondrial Superoxide Production by Paraquat

Abstract: Paraquat (1,1-dimethyl-4,4-bipyridinium dichloride) is widely used as a redox cycler to stimulate superoxide production in organisms, cells, and mitochondria. This superoxide production causes extensive mitochondrial oxidative damage, however, there is considerable uncertainty over the mitochondrial sites of paraquat reduction and superoxide formation. Here we show that in yeast and mammalian mitochondria, superoxide production by paraquat occurs in the mitochondrial matrix, as inferred from manganese superoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
375
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 501 publications
(419 citation statements)
references
References 72 publications
(66 reference statements)
24
375
1
5
Order By: Relevance
“…The results indicated that the herbicide treatment inhibited by 32 % the rotenonesensitive complex I-III activity, which was similar to the data reported in our published work, indicating that the external NADH cytochrome c reductase system does not significantly contribute to NADH oxidation in our assays. It is important to note that the inhibition of complex I and the increase in free radicals production by paraquat has been extensively described in different models of toxicity (Cocheme and Murphy 2008;Drechsel and Patel 2009;Fukushima et al 1993;Tawara et al 1996) and our results were in accordance with those studies.…”
supporting
confidence: 82%
“…The results indicated that the herbicide treatment inhibited by 32 % the rotenonesensitive complex I-III activity, which was similar to the data reported in our published work, indicating that the external NADH cytochrome c reductase system does not significantly contribute to NADH oxidation in our assays. It is important to note that the inhibition of complex I and the increase in free radicals production by paraquat has been extensively described in different models of toxicity (Cocheme and Murphy 2008;Drechsel and Patel 2009;Fukushima et al 1993;Tawara et al 1996) and our results were in accordance with those studies.…”
supporting
confidence: 82%
“…One possible mechanism is that nearby amino acid residues may increase the nucleophilicity of the Cys 2 by lowering its pKa as previously proposed in Drosophila melanogaster TrxR (Williams et al, 2000). At a physiological pH, most Cys with pKa~8.3 will be found in the protonated and thereby rather inert forms, while Sec would mainly be deprotonated and thus more more prone to engage in chemical reaction (Cocheme and Murphy, 2008). However, the actual pKa values of Cys present in protein can be significantly lowered by the combined effects of a number of other residues in the protein, depending on the microenvironment of the polypeptide structure.…”
Section: Discussionmentioning
confidence: 93%
“…The Trx-reducing activity of mammalian TrxR is totally selenium-dependent, which implies that all of the Trx-dependent systems, in fact, are selenium-dependent (Cocheme and Murphy, 2008). The lower pKa of a selenol and the higher nucleophilicity of a selenolate confers a type of "catalytic advantage" over Cys, when attacked position of thiol-disulfide interchange reaction.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of mCAT and cCAT to protect against chronic mitochondrial oxidative stress was assayed by treating mCAT‐ or cCAT‐expressing HEK cells with 5 mM PQ for 48 hr (Supporting Information Figure S2B). PQ diverts electrons out from Complex I of the electron transport chain generating ROS in the mitochondrial compartment (Cochemé & Murphy, 2008). Both CAT constructs prevented PQ‐induced cell death (Figure 1h) and diminished oxidative damage (Supporting Information Figure S2).…”
Section: Resultsmentioning
confidence: 99%